GENRE RECOGNITION TO WRITING CONTROL: DEVELOPING DISCIPLINARY WRITING IN ENGLISH NURSING DOCUMENTATION BY L2 UNDERGRADUATE NURSING STUDENTS - Yoyok Febrijanto (Suluh Adiluhung Publisher (SAPub), 2026)
English nursing documentation requires students to coordinate language proficiency, genre knowledge, and disciplinary communication. Yet relatively limited research has examined how undergraduate L2 writers perform this professional genre in educational settings. This study investigates English nursing documentation produced by L2 undergraduate nursing students as developing disciplinary writing. Using a descriptive mixed-methods text analysis, the study screened 176 portfolio files and analyzed 110 documentation assignments from an undergraduate nursing program of Health Science College of Baptist Hospital, Kediri, East Java, Indonesia. The texts were examined across four dimensions: genre conformity, organization and coherence, language accuracy, and disciplinary terminology. The corpus showed an uneven developmental profile. Genre conformity (M = 2.86) and disciplinary terminology (M = 2.79) were stronger than organization/coherence (M = 1.93) and language accuracy (M = 1.98). Overall, 62 assignments were classified as adequate disciplinary writing, 44 as emerging disciplinary writing, and 4 as weak. Within-text imbalance was common: 60.9% of the assignments showed a gap of at least two points between their strongest and weakest dimensions, and more than half combined adequate genre and terminology performance with weak or emerging performance in coherence and/or language. Writing problems were also cumulative: all texts with zero or one coded problem were classified as adequate, whereas none of the texts with four or five coded problems reached the adequate level. Archive-level variation further suggested that pedagogical context shaped performance, especially in organization/coherence. The findings indicate that English nursing documentation should be understood not merely as a site of language error, but as developing disciplinary writing in which genre recognition often precedes fuller rhetorical and linguistic control. The study supports genre-based, discipline-sensitive, and context-aware writing pedagogy in undergraduate nursing education.